2020
DOI: 10.4236/gep.2020.82006
|View full text |Cite
|
Sign up to set email alerts
|

Historical and Future Spatial and Temporal Changes in Land Use and Land Cover in the Little Ruaha River Catchment, Tanzania

Abstract: Increased anthropogenic activities in the Little Ruaha River Catchment have modulated the catchment condition, nevertheless, the future changes as a result of increased anthropogenic activities are unknown. Understanding the future changes is vitally important for the design of appropriate strategies towards sustainable management of the catchment resources. This study applied Remote Sensing and GIS techniques (Jensen & Lulla, 1987) to assess the historical long-term changes in land use and land cover using La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The combined classification included both supervised classification and unsupervised classification methods, which are broadly used in land cover classification. The maximum likelihood algorithm (MLC) is the most commonly used method in supervised classification with remotely sensed image data [3], which computes the posterior possibility of a pixel fitting into the corresponding class based on the Bayes theorem [34]. The Universal Transverse Mercator (UTM) map coordinate system, Zone 48 North, and Datum Arc 1984 (WGS_1984_UTM_ZONE_48N) were used in these images.…”
Section: Image Processing and Data Analysismentioning
confidence: 99%
“…The combined classification included both supervised classification and unsupervised classification methods, which are broadly used in land cover classification. The maximum likelihood algorithm (MLC) is the most commonly used method in supervised classification with remotely sensed image data [3], which computes the posterior possibility of a pixel fitting into the corresponding class based on the Bayes theorem [34]. The Universal Transverse Mercator (UTM) map coordinate system, Zone 48 North, and Datum Arc 1984 (WGS_1984_UTM_ZONE_48N) were used in these images.…”
Section: Image Processing and Data Analysismentioning
confidence: 99%
“…Spatial data includes 30 m resolution digital elevation model (DEM) downloaded from NASA (https://reverb.echo.nasa.gov). The digital Open Journal of Modern Hydrology LULC map (Figure 2) of the study area for 1990, 2015 and 2040 obtained from LULC change analysis reported by [22], mapped based on Landsat TM for 1990 and Landsat OLI for 2015 (http://earthexplorer.usgs.gov). Land use/land cover for the year 2040 was projected based on CA-Markov chain analysis.…”
Section: Swat Model Inputsmentioning
confidence: 99%
“…Results (Appendix 1 and Appendix 2) indicate that land use and land cover change between 1990 and 2015 and the projected land use/cover for the year 2040 as reported by [22]. The report detailed the decrease in forest, riverine for-…”
Section: Land Use Land Cover Change Analysismentioning
confidence: 99%
“…Other researchers [14,15] carried out hydrological studies in the Mbarali River and Wami river subbasins, respectively, highlighting the impacts of climate change and landcover dynamics on river flows. The consequences of land cover dynamics on catchment hydrology have equally been conducted in the Little Ruaha River catchment [16]. Some studies, albeit scanty, that aimed at assessing the impact of land cover changes on groundwater recharge in Tanzania have been carried out in the northern part of Tanzania recently [17,18].…”
Section: Background Informationmentioning
confidence: 99%